Responsibility and Language Practices in Place - Siragusa, Laura; Ferguson, Jenanne K. (Studia Fennica Anthropologica, 2020)
This volume includes chapters by junior and senior scholars hailing from Europe, Asia, North America, and Oceania, all of whom sought to understand the social and cultural implications surrounding how people take responsibility for the ways they speak or write in relation to a place-whether it is one they have long resided in, recently moved to, or left a long time ago.;The contributors to the volume investigate 'responsibility' in and through language practices as inspired by the roots of the (English) word itself: the ability to respond, or mount a response to a situation at hand. It is thus a 'responsive' kind of responsibility, one that focuses not only on demonstrating responsibility for language, but highlighting the various ways we respond to situations discursively and metalinguistically. This sort of responsibility is both part of individual and collectively negotiated concerns that shift as people contend with processes related to globalization.